2014
DOI: 10.1016/j.micres.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and molecular profiling of class 1 integrons in MDR Acinetobacter baumannii isolates and whole genome-based analysis of antibiotic resistance mechanisms in a representative strain

Abstract: The class 1 integron is an important driver of the nosocomial dissemination of multidrug-resistant (MDR) bacteria, such as Acinetobacters. In this study, we characterized the gene cassette arrays of class 1 integrons in Acinetobacter baumannii, where the detailed structure of these integrons for 38 clinical strains was analyzed. The results showed that there are three types of gene cassette arrays that are carried by different class 1 integrons, among them the aac(6')-IId-catB8-aadA1 array was the most prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Our results indicated that 30.3% of isolates were resistant to 4–6 antimicrobial agents and 4.5% were resistant to 7–9 antimicrobials. This indicated that antimicrobial resistance among Salmonella isolates from retail meat in Hubei Province was lower than that in other areas of China (Zhu et al, 2014; Wang et al, 2017). In our study, the highest rates of antimicrobial resistance were to the sulfonamides, tetracycline, amoxicillin, ampicillin and chloramphenicol.…”
Section: Resultsmentioning
confidence: 89%
“…Our results indicated that 30.3% of isolates were resistant to 4–6 antimicrobial agents and 4.5% were resistant to 7–9 antimicrobials. This indicated that antimicrobial resistance among Salmonella isolates from retail meat in Hubei Province was lower than that in other areas of China (Zhu et al, 2014; Wang et al, 2017). In our study, the highest rates of antimicrobial resistance were to the sulfonamides, tetracycline, amoxicillin, ampicillin and chloramphenicol.…”
Section: Resultsmentioning
confidence: 89%
“…In addition, the sulfonamide resistance genes sul1 and sul2 were present in 5 strains and 2 strains, respectively,28 the quinolone resistance genes AAC(6ʹ)-Ib9 and AAC(6ʹ)-Ib’ were found in only 2 strains,29 and the chloramphenicol resistance gene catB8 was present in 4 strains 30. With the exception of MDR-CQF, the other 9 strains each contained the tetracycline resistance-related gene tet (B),31 the macrolide resistance-related gene msrE,32 and the aminoglycoside resistance-related gene armA 33…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted by Nasr et al (14), a high rate of resistance to amikacin (90%) and gentamicin (85%) was reported. Zhu et al (15) reported that among 39 A. baumannii isolates tested, 33 (84.6%) were resistant to gentamycin and 32 (82.1%) were resistant to amikacin. In another study form Taiwan, the rates of resistance to gentamycin and amikacin were 57.5% and 56.7%, respectively (16).…”
Section: Discussionmentioning
confidence: 99%